Analisis Kesesuaian Lahan Budidaya Ikan dalam Mendukung Pengembangan Minapolitan Kawasan Pesisir Kabupaten Lampung Selatan - Mia Ermawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The coastal area of South Lampung has considerable fishery potential, both capture and cultivation fisheries. The high potential of fisheries has made South Lampung designated as a minapolitan area with a center for aquaculture. However, high exploitation and uncontrolled human activity patterns have resulted in environmental degradation such as a decrease in the quality of marine waters and the aquaculture environment which has an impact on the continuity of fishery production. Seeing there are problems, it is necessary to carry out a land suitability analysis to see a suitable location for fish cultivation to support minapolitan development this area. This study used statistical descriptive analysis and overlay analysis to identify suitable locations for fish farming. Through the use of this analysis technique, a location that is very suitable for fish farming in the coastal area of South Lampung is obtained, including Pulau Tiga and Batumandi Island.